Heirs and Inheritance Law from the Perspective of Hadith: Protection of Family Rights - Ahmad Idus Showabi; Muhammad Wahibul Minan (Yayasan Insan Mulia Bima, 2025)
Muslims always talk about the distribution of inheritance. This is because the division of inheritance is a problem that is directly related to daily life. In addition, Islamic inheritance law is often criticized by gender equality activists. However, the jurists (Islamic jurists) are of the opinion that the verses in the Qur'an that explain the parts of the heirs are verses that are qath'i al-dilalah, which means that the law is certain, so it is impossible to make ijtihad about it. A few people consider this distribution of inheritance to be unfair in some circumstances. For example, a boy is usually educated more than a girl in most societies. However, during the distribution of inheritance, boys receive twice the share of girls during the distribution of inheritance. In fact, a Testament is one way to accomplish this. But the Testament must not exceed 1/3 of the inheritance, and must have the approval of the other heirs. This is where additional questions arise about what a Testament and inheritance are, as well as who is entitled to give or receive a Testament. In this paper, quantitative approaches Testament be used, including case approaches, historical approaches, comparative approaches, and conceptual approaches. Quantitative analysis Testament be used to develop and use mathematical models, theories, and hypotheses on the problem of inheritance distribution based on Testaments from the perspective of ushul fiqh and Islamic legal philosophy.